Analysis Tower Bts Sst 4 Leg Angular 42m Due To Extend and Additional Antenna Load: Case Study of The Semayap Kotabaru Location - Arif Johansyah; Agyanata Tua Munthe (Journal of World Conference (JWC), 2021)
In BTS tower planning, the load that affects is the tower load itself, live load and lateral (side) loads that have a dominant effect is wind loads, because wind loads have high sensitivity to steel construction buildings (have a mass that tends to be light). Wind loads are calculated according to the Telecommunications Industry Association and Electronic Industries Alliance (TIA / EIA) standard structural standards for steel antenna tower and antenna supporting structure (TIA / EIA-222-G, 2005). The analysis uses the MS Tower V6 program, as an application to simplify telecommunication tower modeling. The purpose of this paper is to find alternative tower reinforcement so that it can withstand additional loads, be it additional loads due to extend and additional loads due to the proposed antenna.Based on the analysis results, the existing tower is still safe with a ratio of 0.345 <1, but the tower with an additional height and additional load of the antenna is not safe with a ratio of 1.189> 1, and the tower after being strengthened on the tower leg with a height of 0m-36m is done with STA (Star Angle) . And for reinforcement for leg towers at a height of 36-40m, it is done by adding the redundant member to the tower ratio to 0.689 <1, which means it is categorized as safe.Analysis with operational wind load (84km / hour), the reinforcement tower can withstand a maximum twist of 0.3436, a maximum sway of 0.0413, a maximum displacement of 0.1402.